(untitled) (Boca Raton, FL, 2000)
Based on work with more than 30 industrial and academic organizations, including Nestle, Unilever, and Danone, Managing Frozen Foods provides a unique overview of the entire supply chain. Noting the key quality factors at each stage of production, distribution and retail sales of frozen food, this book will demonstrate why quality is a fundamental advantage in this multi-billion dollar industry
Quá trình nhiệt độ thấp trong chế biến thực phẩm
Keywords: Frozen foods